Evaluation of Genetic Diversity and Host Resistance to Stem Rust in USDA NSGC Durum Wheat Accessions. Issue 2 (1st July 2017) - Chao, Shiaoman; Rouse, Matthew N.; Acevedo, Maricelis; Szabo‐Hever, Agnes; Bockelman, Harold; Bonman, J. Michael; Elias, Elias; Klindworth, Daryl; Xu, Steven
Abstract : The USDA–ARS National Small Grains Collection (NSGC) maintains germplasm representing global diversity of small grains and their wild relatives. To evaluate the utility of the NSGC durum wheat ( Triticum turgidum L. ssp. durum ) accessions, we assessed genetic diversity and linkage disequilibrium (LD) patterns in a durum core subset containing 429 lines with spring growth habit originating from 64 countries worldwide. Genetic diversity estimated using wheat single‐nucleotide polymorphism (SNP) markers showed considerable diversity captured in this collection. Average LD decayed over a genetic distance to within 3 cM at r 2 = 0.2, with a fast LD decay for markers linked at >5 cM. We evaluated accessions for resistance to wheat stem rust, caused by a fungal pathogen, Puccinia graminis Pers. Pers. f. sp. tritici Eriks. and E. Henn ( Pgt ), using races from both eastern Africa and North America, at seedling and adult plant stages. Five accessions were identified as resistant to all stem rust pathogen races evaluated. Genome‐wide association analysis detected 17 significant associations at the seedling stage with nine likely corresponding to Sr7, Sr12, and Sr13 and the remaining potentially being novel genes located on six chromosomes. A higher frequency of resistant accessions was found at the adult plant stage than at the seedling stage. However, few significant associations were detected possibly a result of strong G × E interactions not properly accounted for in the mixed model. Nonetheless, the resistant accessions identified in this study should provide wheat breeders with valuable resources for improving stem rust resistance.